88 NATIONAL ANTIMICROBIAL POINT PREVALENCE SURVEY IN HSE OLDER PERSONS RESIDENTIAL CARE FACILITIES (OPS-RCFS). (25th October 2022) - Clancy, A; Regan, M; Armitage, S; Shah, M; Mannion, C; Gallagher, O; Foran, R; Fagan, S; Donnelly, M; Love, B
Abstract: Background: The HALT study in 2016 found that residents in Irish OPS RCFs were twice as likely to be on systemic antimicrobial compared with European average (10% v 5%). National antibiotic prescribing guidelines are available at www.antibioticprescribing.ie and prescribers are encouraged to choose 'green' (preferred) over 'red' (reserved) agents. HSE Community Antimicrobial Pharmacists (AMPs) have been employed since 2020. We aimed to establish the quality and quantity of antimicrobial prescribing in OPS-RCFs to inform antimicrobial stewardship activities. Methods: All residents in HSE OPS-RCFs were surveyed between October 2020 and August 2021. AMPs reviewed all medication charts for systemic antimicrobials prescribed within previous 30 days. Medical notes +/- laboratory results were reviewed for persons on antimicrobials. Adherence to guidelines was assessed and information obtained on practices related to antimicrobial use. Results: The survey included 4, 448 individuals in 121 OPS RCFs. 12% were on systemic antimicrobial at time of survey. 27% received an antimicrobial in the previous 30 days. 50% of antibiotic use on survey day was for prophylaxis (6.3% of all residents). Prophylaxis exceeded 6 months in 66% persons, and 12 months in 57%. There was high usage of green versus red agents (65% vs 30%). Co-amoxiclav (red) was most commonly prescribed antimicrobial to treat infection (19%). 42% of sites reported routine use of dipstick urinalysis to support diagnosis of UTI in asymptomatic residents. 36% of sites did not have onsite electronic laboratory access. 61% of facilities did not record residents' pneumococcal vaccination status. Conclusion: Key national recommendations: Review all UTI prophylaxis within 6 months of initiation with view to de-prescribing. Cease routine use of dipstick urinalysis to support diagnosis of UTI for asymptomatic persons. Electronic access to laboratory results on-site required to support timely decision-making. All staff should be aware of the national antimicrobial guidelines. Pneumococcal vaccine status should be determined, and provided as necessary.